Thermal Design and Simulation of High Power Press-pack IGBT Module - XIAO Hongxiu; DOU Zechun; PENG Yongdian (Kongzhi Yu Xinxi Jishu)
With the improvement of packaging power level of IGBT module, power density and operating temperature on chip will rise, which may lead to an increasing affect of thermal stress on long-term reliability of the device. Taking 3 300 V/3 000 A press-pack IGBT module as example, it studied thermal resistance of the press-pack IGBT, analyzed its heat conduction model and took iterative calculation on module structure with ANSYS. The results show that the double-side heat dissipation structure is asymmetry. Furthermore, influence of the structure on heat resistance was analyzed and an optimized method was proposed aiming to the structure parameters such as area and thickness of electrode pad, thickness of molybdenum plates, etc., which could provide a reference for design optimization of IGBT device.